2022
DOI: 10.1038/s41467-022-35306-1
|View full text |Cite
|
Sign up to set email alerts
|

Targeting endogenous kidney regeneration using anti-IL11 therapy in acute and chronic models of kidney disease

Abstract: The kidney has large regenerative capacity, but this is compromised when kidney damage is excessive and renal tubular epithelial cells (TECs) undergo SNAI1-driven growth arrest. Here we investigate the role of IL11 in TECs, kidney injury and renal repair. IL11 stimulation of TECs induces ERK- and p90RSK-mediated GSK3β inactivation, SNAI1 upregulation and pro-inflammatory gene expression. Mice with acute kidney injury upregulate IL11 in TECs leading to SNAI1 expression and kidney dysfunction, which is not seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 61 publications
2
33
0
Order By: Relevance
“…Among the five cytokines related to lipid metabolism and adipogenesis that increased in SNx obese rats, the presence of IL11 should be noted. IL11 is an important downstream regulator of TGF-β and has been recently described as a pro-fibrotic factor in fibroblasts as well as in a mouse model of acute kidney injury [34,54,55]. In our SNx obese model, this cytokine could be linked to the worsened CKD and renal fibrosis, as IL11 release in the circulation by adipose tissue can stimulate renal epithelial cell mesenchymal transition and dysfunction, as has been previously demonstrated in cultured cells [34,56,57].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Among the five cytokines related to lipid metabolism and adipogenesis that increased in SNx obese rats, the presence of IL11 should be noted. IL11 is an important downstream regulator of TGF-β and has been recently described as a pro-fibrotic factor in fibroblasts as well as in a mouse model of acute kidney injury [34,54,55]. In our SNx obese model, this cytokine could be linked to the worsened CKD and renal fibrosis, as IL11 release in the circulation by adipose tissue can stimulate renal epithelial cell mesenchymal transition and dysfunction, as has been previously demonstrated in cultured cells [34,56,57].…”
Section: Discussionsupporting
confidence: 58%
“…Preadipocyte factor 1 (Pref-1) [28], fibroblast growth factor 21 (FGF-21) [29], leukemia inhibitory factor (LIF) [30], angiopoietinlike 3 [31], and interleukin 11 [32,33], all implicated in lipid metabolism or adipogenesis, were significantly increased in both Cafeteria groups compared to their corresponding Standard groups (Table 2). Interestingly, interleukin 11 (Il11) has pro-fibrotic properties in the kidney [34]. The dipeptidyl peptidase 4 (DPP4), which plays a major role in glucose metabolism and may be implicated in fibrosis [35,36], was also increased in Cafeteria-SNx rats compared to Standard-SNx (Table 2).…”
Section: Inflammation In Kidney and Ewatmentioning
confidence: 99%
“…As expected, IL11 activates JAK/STAT3 in human fibroblasts and epithelial cells (e.g. renal tubular epithelial cells (TECs) and hepatocytes) [ 70–72 , 74 ]. While IL11-stimulated ERK activation is biphasic and prolonged, the activation of JAK/STAT in cultured fibroblasts and TECs is immediate, transient and lesser in magnitude when compared with the effects of IL6 or OSM.…”
Section: Il11 Signallingmentioning
confidence: 59%
“…In our studies, and those of others, IL11-stimulated MEK/ERK activation has been identified as particularly important for fibroblast mesenchymal (myofibroblast) transition (FMT) and also VSMC mesenchymal transition (VMT), referred to as phenotypic switching [ 67–69 ]. MEK/ERK is a recognised non-canonical signalling pathway downstream of gp130 and is activated in a biphasic manner by IL11 in vitro with an initial phase that can be attenuated by increased DUSP activity and a later phase that is sustained [ 70–74 ]…”
Section: Il11 Signallingmentioning
confidence: 99%
See 1 more Smart Citation